THE DYNAMICS OF DIVORCE LAW IN ISLAM: A COMPARATIVE STUDY OF THE PROVISIONS ON TALAK, KHUL’, AND JUDICIAL DIVORCE IN INDONESIA AND MOROCCO - Ihsan Siregar; Sukiati Sukiati; Iwan Iwan (Universitas Islam Negeri Sumatera Utara Medan, 2026)
Morocco, by way of the Mudawwanah al-Usrah (2004), and Indonesia, through the Marriage Law in conjunction with the Compilation of Islamic Law (KHI), have undertaken reforms to their respective Islamic family law systems aimed at curbing unilateral divorce and safeguarding women's rights through an enhanced judicial role. This study seeks to comparatively examine the concepts, procedural frameworks, and practical implementations of three divorce mechanisms—talaq (repudiation), khul' (compensatory dissolution), and judicial divorce—within the legal contexts of Morocco and Indonesia. A normative-comparative legal approach is employed, drawing on both statute analysis and cross-jurisdictional comparison. Findings indicate the following. In terms of Talaq: Indonesian law mandates that talaq declarations be made before the Religious Court, while Moroccan law imposes more rigorous judicial oversight, conditioning talaq authorization on the husband's prior settlement of all financial obligations to the wife, including mut'ah. Regarding Khul': Indonesian law incorporates khul' within the mechanism of Cerai Gugat (wife-initiated divorce) accompanied by a compensatory payment (iwadh), whereas Moroccan law treats khul' as a distinct financial arrangement, with judges holding authority to determine compensation in cases of dispute. As for Judicial Divorce: both countries have broadened the grounds upon which a wife may petition for divorce; however, Morocco demonstrates greater progressiveness through the introduction of the Shiqaq doctrine (irreconcilable differences), which permits dissolution without requiring exhaustive proof of fault. In conclusion, while both nations have effectively transferred divorce authority from the private domain to the judiciary, Morocco's approach is more systematically codified and progressive in constraining husbands' prerogatives, whereas Indonesia continues to rely on a multi-tiered mediation framework alongside a dual administrative track for divorce proceedings.